Surgical Treatment of Stenosing Tenosynovitis: Early and Late Outcomes, Complications: Surgical treatment of stenosing tenosynovitis is effective. However, for some patients it might cause discomfort of the hand because of scarring. - Varkalys, Karolis; Knystautas, Saulius; Braziulis, Kęstutis; Tamaliūnas, Vytautas; Zacharevskij, Ernest (Lietuvos chirurgija, 2023)
Background. The thickening of A1 pulley of the tendon sheath limits the excursion of flexor tendon. Stenosing tenosynovitis causes finger movements dysfunction and pain. Objective. To analyze early and late outcomes of patients with stenosing tenosynovitis after surgical treatment – anulotomy. Methods. All patients had standard surgical procedure – open anulotomy of A1 pulley. Pain (verbal pain scale), hand and arm function (QuickDASH) and complications were recorded before surgery, after 1 week, 3 months and 6 months post surgery. Results. There were 45 patients, 29 (64%) female, 16 (36%) male. The highest pain score was recorded before surgery median 5 (IQR 5). The lowest pain score median 2 (IQR 2) was recorded after 6 months post surgery. The difference of the results after 1 week, 3 months and 6 months was statistically significant p
Keywords: stenosing tenosynovitis; trigger finger; anulotomy; surgical treament